Effectiveness of the habitual offender act: An assessment of criminal histories - Sigler, Robert (American journal of criminal justice, 1990)
Habitual offender acts have been adopted by 43 states and are under consideration in the legislatures of others. These acts have been adopted with relatively little evaluation of the costs involved in the implementation of this legislation. This study seeks to evaluate the extent to which Alabama’s habitual offender statute captures serious career criminals. The results indicate that the differences between those in the prison population sentenced under habitual offender statutes and those sentenced under other statutes is not significant. There does appear to be support for the contention that the majority of prisoners have substantial criminal histories; however, it is noted that many have not committed a severe crime. The exaggerated claims for the number of crimes committed by “typical” offenders and resultant high costs of non-incarceration are examined and challenged. The authors suggest that the resources available to deal with offenders could be better invested in the development and testing of community-based programs designed to divert offenders from a life of crime rather than in programs which intervene after criminal histories are severe and which invoke life-long incarceration as a remedy.